Strategies for promoting green buildings: integrating evolutionary game and SEIR models - Song Wang; Dongliang Zhu (Scientific Reports)
Abstract The use of green buildings is an inevitable requirement for sustainable development. However, green buildings face the awkward situation of a slow market share increase. This study explores the changing strategies of government and developers in promoting green buildings and how they affect consumer acceptance, providing an interdisciplinary theory for promoting green buildings. Based on the stakeholder analysis, this study constructs an evolutionary game model of the government and developers. Through analyzing consumer behavioral shifts, SEIR modeling was conducted by comparing the use of green buildings to an “infectious disease”. The findings indicate that balanced government strategies of rewards and punishments are crucial for encouraging developers to promote green buildings and encouraging developers to promote green buildings. The costs and benefits for developers significantly influence their willingness to adopt green building practices. The costs and benefits for developers significantly influence their willingness to adopt green building practices. In addition, the study found that even stable promotion strategies need to be adapted to changes in consumer behavior. This interdisciplinary research approach provides a new perspective on the adaptability of green building promotion strategies. This study provides a foundation and theoretical support for green building promotion.